Second Trimester Cervical Length and Its Association with Vaginal Birth after Cesarean Delivery - Nicholas, Sara S.; Orzechowski, Kelly M.; Berghella, Vincenzo; Baxter, Jason K. (American Journal of Perinatology, 2016)
Objective This study aims to evaluate the relationship between cervical length (CL) and trial of labor after cesarean (TOLAC) delivery.Study Design This retrospective cohort study evaluated second trimester CL and likelihood of successful TOLAC. Women undergoing TOLAC from January 2009 to December 2011 who underwent transvaginal ultrasound CL between 180/7 to 236/7 weeks gestation were included. The threshold for CL was assessed using a receiver operating characteristics curve, with ≥ 45 mm determined to be the optimal threshold. Women with CL < 45 mm were compared with women with CL ≥ 45 mm with respect to TOLAC. Multivariate analysis was used to assess the association of CL with TOLAC.Results A total of 45 patients met inclusion criteria, 14 (31%) with a long CL (≥ 45 mm) and 31 (69%) with CL < 45 mm. Groups did not differ in demographics or factors predictive of vaginal birth after cesarean (VBAC) delivery. More women with CL < 45 mm had successful VBAC (81%) than women with long CL (43%, relative risk 1.9, p = 0.03). Prior vaginal delivery and CL < 45 mm were both significant predictors of VBAC (odds ratio 1.8 and 2.0, respectively).Conclusion CL < 45 mm is associated with VBAC.
Keywords: cervical length; CL; vaginal birth after cesarean delivery; VBAC; trial of labor after cesarean; TOLAC